Experimental Research on the Setting up and Exploitation of the Human Prehistoric Habitat in the Middle Dniester Region - I. Niculiţă; S. Matveev; A. Nicic; A. Corobcean (EXARC Journal)
The research of archaeological monuments in the Middle Dniester basin over the last two decades has highlighted a series of new data on the evolution of human communities during the first Iron Age (8th to 10th centuries BC), demonstrating the advanced level and original character of Cozia-Saharna communities (Каshuba, 2000; Niculiţă and Nicic, 2002; Niculiţă, et al., 2003; Niculiţă and Nicic, 2007; Niculiţă, Zanoci and Arnăut, 2007; Zanoci and Băţ, 2007; Kašuba, 2008, p.40; Niculiţă and Nicic, 2008; Niculiţă, et al., 2008).